Hamstring and ACL injuries impacts on hamstring-to-quadriceps ratio of the elite soccer players: A retrospective study - Alizadeh, Shahab; Sarvestan, Javad; Svoboda, Zdeněk; Alaei, Fatemeh; Linduška, Petr; Ataabadi, Peyman Aghaie (Physical therapy in sport, 2022)
This study aimed to compare the angle-specific (AS) and non-angle-specific (NAS) hamstring to quadriceps conventional and functional ratios between healthy, hamstring- and ACL-injured elite soccer players. One hundred and eleven players (27.42 ± 8.01 years, 182.11 ± 6.79 cm, 75.93 ± 7.25 kg) completed a series of concentric knee flexor and extensor strength in addition to eccentric knee flexor strength was measured at an angular velocity of 60°.s-1. Normalized and raw peak torque values, and the torque-angle profiles were extracted for analysis. Conventional and functional NAS (peak values) and AS (waveform ratios) hamstring to quadriceps ratios were calculated and compared between the groups. Healthy players produced greater functional and conventional ratios compared to players with either ACL or hamstring injury. Players with hamstring injury produced a lower AS functional ratios between 46° and 54° of knee flexion. Players suffering from ACL injury depicted a lower value for the AS functional ratio between 33° and 56° of knee flexion. Although NAS can identify soccer players with previous hamstring or ACL injury, the range where there is a strength deficiency is eluded. With the use of AS the range where the deficiency is present can be identified, and clinicians can benefit from this analysis to design robust rehabilitation protocols.
Keywords: točivý moment; Muscle Strength; Soccer; svalová síla; čtyřhlavý sval stehenní; lidé; fotbal; poranění předního zkříženého vazu; zadní stehenní svaly; Quadriceps Muscle; Torque; retrospektivní studie; Humans; Hamstring Muscles; Retrospective Studies; Anterior Cruciate Ligament Injuries